A narrative meta-synthesis of how people with schizophrenia experience facilitators and barriers in using antipsychotic medication: Implications for healthcare professionals. (September 2018) - Salzmann-Erikson, Martin; Sjödin, Marie
Abstract: Background: It is recognized that people who are diagnosed with schizophrenia often do not fully adhere with their antipsychotic prescription. The vast majority of previous research on the topic of medical adherence is limited to quantitative research methods, and in particular, to determining correlations. Objectives: The present review was designed to describe how people who are diagnosed with schizophrenia experience and narrate pharmacological treatment with antipsychotic medication. Design: A narrative meta-synthesis. Data sources/review method: A search was conducted in three databases, PubMed, CINAHL and PsycINFO, to identify qualitative original research. Nine articles met the criteria for inclusion and were subjected to a qualitative interpretive meta-synthesis. Results: The findings showed that patients were uninformed about medication but valued talks about medication with professionals. The findings also demonstrated that patients are motivated to take medication in order to gain stability in their life and to be able to participate in life activities and in relationships. Good support, both from relatives and professionals, also motivates them to continue taking medication. The obstacles were side-effects, pressure and compulsion, and rigid organizations. Conclusions: We advise professionals to adopt a person-centered approach to healthcare when encountering these patients and to transform the language used to describe patients from terms denoting compliance and adherence to terms denoting cooperation and alliance. Labeling patients as compliant or non-adherent may risk fortifying preconception of patients as static beings and obscure the patients' individual recovery process.